Thermal expansion behavior of (Bi0.5Na0.5)Zr 1- xTix O3 ceramics - Jaiban P. (2014)
(Bi0.5Na0.5)Zr1-xTixO 3 with x = 0, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6 ceramics were fabricated by a conventional sintering technique at 850-950°C for 2 h. From X-ray diffraction study, three regions of different phases were observed in the ceramic system; i.e., orthorhombic phase region (0 ≤ x ≤ 0.2), mixed-phase region (0.3 ≤ x ≤ 0.4), and rhombohedral phase region (0.5 ≤ x ≤ 0.6). The thermal expansion coefficient data indicated the phase transition in the temperature range from 100°C-150°C of the ceramics. The thermal strain curve of all compositions suggested a decrease of local polarization with temperature increment up to the Burns temperature. © 2013 Copyright Taylor and Francis Group, LLC.